(3CKQ eeGQSGJ GdeSDhdjI GdGLJeGYjI Ydi GdCOGA GdJfXjej aj eQGcR JCgjd GdCWaGd Phj GdGMJjGLGJ GdNGUI HGdbWGY GdUMj (B/s - (3,QfG eLOj eUWai eMehOs; (3QZOI CHh GdSYhO CMeO jhfSs; (3gfO eMeO fLjH s (2024)
(3GdgOa(B: (3JYJHQ eeGQSGJ GdeSDhdjI GdGLJeGYjI VQhQjI aj GdeLJeY, hHUag NGUI aj eQGcR JCgjd GdCWaGd Phj GdGMJjGLGJ GdNGUI, hjJeKd GdZQV ef gPg GdOQGSI aj GdJYQa Ydi CKQ eeGQSGJ GdeSDhdjI GdGLJeGYjI HCHYGOgG (B((3GdeSDhdjI GdGbJUGOjI, GdeSDhdjI GdbGfhfjI, GdeSDhdjI GdCNdGbjI, GdeSDhdjI GdNjQjI(B) (3Ydi GdCOGA GdJfXjej HCHYGOg (B((3GdCOGA GdeGdj, GdCOGA GdJTZjdj(B). - (3GdefgLjI(B: (3Je GSJNOGe GdefgL GdhUaj GdJMdjdj GdEMUGFj dOQGSI GdYdGbI Hjf GdeJZjQGJ, hJe GdGYJeGO Ydi bGFeI GdGSJbUGA cCOGI dLeY GdHjGfGJ, hJe JMOjO eLJeY GdHMK hgh eOjQjf eQGcR JCgjd GdCWaGd Phj GdGMJjGLGJ GdNGUI, hJeKd GdeLJeY aj (B(68) (3eQckRG, hJe GdMUhd Ydi (B(303) (3GSJLGHI ef eOjQjf eQGcR JCgjd GdCWaGd Phj GdGMJjGLGJ GdNGUI, hJe GSJNOGe GdJMdjd GdEMUGFj(B. Smart PLS(3HGdGYJeGO Ydj HQfGeL (B- (3GdfJGFL(B: (3JhUdJ GdOQGSI Edi Cf gfGc JCKjQkG EjLGHkqjG deeGQSGJ GdeSDhdjI GdGLJeGYjI Ydi GdCOGA GdJfXjej aj eQGcR JCgjd GdCWaGd Phj GdGMJjGLGJ GdNGUI HGdbWGY GdUMj(B. - (3GdJhUjGJ(B: (3JbJQM GdHGMKI eLehYI ef GdJhUjGJ CgegG(B: (3EfTGA gjFI eSJbdI ddeSDhdjI GdGLJeGYjI JGHYI dQFGSI eLdS GdhRQGA GdeUQj, JSYj dJYRjR KbGaI GdeSDhdjI GdGLJeGYjI hJWHjb eeGQSGJgG OGNd GdgjFGJ hGdLgGJ hGdeQGcR GdQSejI GdeUQjI(B.s
Purpose: This study aimed to examin the impact of corporate social responsibility (CSR) ( economic, legal, ethical, and philanthropic practices) on the organizational performance ( financial and operational performance) in rehabilitation centers for children with special needs. -Methodology: A descriptive-analytical research methedology was employed to investigate the relationship between the selected variables. The population for this study was the managers working in the rehabilitation centers for children with special needs in Great Cairo ( the total number of these centers is 68). However, the valid-collected questionnaires was 303. Smart PLS was used for statistical analysis.-Results: This study found that there is a positive effect for CSR practices on organizational performance in rehabilitation centers for children with special needs. -Recommendations:Researcher provided several recommendations.,including establishment of an independent institution under the Egyptian Cabinet responsible for promoting CSR culture and implementing its practices within Egyptian government agencies, institutions, and centers.
(3CWQhMI (B((3eGLSJjQ(B)-(3LGeYI GdbGgQI, (B2024. s
(3HHdjhLQGajG(B: (3UaMGJ (B132-152.s
(3UOQ CjkVG cbQU eOeL(B.s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GOGQI GdGYeGds; (3GdGWaGd GdThGPs; (3GdeSDhdjI GdGLJeGYjI s -- (3GdCOGA GdJfXjejs -- (3eQGcR JCgjd GdCWaGd Phj GdGMJjGLGJ GdNGUIs